1984
DOI: 10.1139/v84-440
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes in organic synthesis. 32. Stereospecific horse liver alcohol dehydrogenase-catalyzed oxidations of exo- and endo-oxabicyclic meso diols

Abstract: . J. Chem. 62, 2578Chem. 62, (1984.Preparative-scale horse liver alcohol dehydrogenase-catalyzed oxidation of meso exo-and endo-7-oxabicyclo[2.2. llheptane diols provides a direct one-step route to enantiomerically pure chiral y-lactones of the oxabicyclic series.J. BRYAN JONES et CHRISTOPHER J. FRANCIS. Can. J. Chem. 62, 2578Chem. 62, (1984.L'oxydation prkparative, catalysCe par I'alcool dCshydrogCnase du foie de cheval, des oxa-7 bicyclo[2.2.1] heptanediols-exo et -endo miso s'avkre &tre une route direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Enzymes have also been used in oxidative and reductive processes. Jones showed that oxabicyclic diol 18 was selectively oxidized by horse liver alcohol dehydrogenase (HLADH) in the presence of nicotine adenine dinucleotide (NAD) and flavin mononucleotide (FMN) to give lactone 19 in 83% yield and >98% ee (eq 2) …”
Section: Introductionmentioning
confidence: 99%
“…Enzymes have also been used in oxidative and reductive processes. Jones showed that oxabicyclic diol 18 was selectively oxidized by horse liver alcohol dehydrogenase (HLADH) in the presence of nicotine adenine dinucleotide (NAD) and flavin mononucleotide (FMN) to give lactone 19 in 83% yield and >98% ee (eq 2) …”
Section: Introductionmentioning
confidence: 99%
“…Hydrogenation of 3c with 10% palladium on carbon in ethyl acetate afforded only the endo isomer 11 in 94% yield. The exo hydrogen at C-3 was assigned by comparing its coupling constant to the bridge proton H 4 ( J 3,4 = 5.2 Hz) with the structually related literature precedent (∼5 Hz for an exo hydrogen versus ∼0 Hz for an endo hydrogen). Treatment of 11 with 0.2% HCl in aqueous THF afforded cyclohexanone 12 in 80% yield. No epimerization was detected by 1 H NMR during the hydrolysis.…”
mentioning
confidence: 99%
“…The double oxidation of alcohols at the expense of molecular oxygen allowed the transformation of primary alcohols to carboxylic acids. In very early work horse liver alcohol dehydrogenase (HLADH) was employed for this type of transformation; thus, a single enzyme was doing two subsequent oxidation steps using FMN for NAD + recycling. , In a related fashion an α-keto acid (α-keto adiapate) was used as oxidant . More recently, engineered variants of galactose oxidase (GalOx) from Fusarium graminearum have been employed in combination with aldehyde oxidases.…”
Section: In Vitro Cascades Requiring For Each Step a Biocatalystmentioning
confidence: 99%